Toward a Common European Union Energy Policy Problems, Progress, and Prospects - Birchfield, V.; Birchfield, V.; Duffield, J.; Duffield, J. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Since the mid-2000s, the European Union has made unprecedented strides toward the creation of a common energy policy. This book takes stock of these developments, evaluating how much progress has actually been made and what remains to be done, what factors explain these recent advances and their limitations.